LANDASAN FILOSOFIS PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL - Tumanggor, Rusmin (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2007)
Peoples had equality of living right. To moved, to creation, to critics, to request or to reject, obedient or denial, to defend our self in all of situation to fulfill the opinion of living need. This condition must be democratic protection. The bone as much white, the blood as much red, to ramble and to buried around in the surface of the world. World view of Manado, â€œall of peoples always friendshipâ€, World view of Melayu â€œThe world where to stand, there the sky to upholdâ€. To share joys and sorrows, utopist of Indonesia. The meaning of lived reality everybody separated with the differences, especially for the indigenous people. So, we must build their solidarity to improve their live and leave the backward. The concept of philosophy based on the universe components. Key Words : philosophy, empowerment, indigenous people